Three-Dimension Numerical Simulation of Scour Temporal Changes due to Flow in the Downstream of Combined Weirs and Gate Model - Yaser Sadeghi Googheri; Mojtaba Saneie; Sirous Ershadi (Salehan Institute of Higher Education, 2017)
Most of weirs create a region with relatively static water in upstream, which can be the place of sediments and wastes deposition in water. Sediments accumulation in upstream changes flow conditions. In this case, combined weir and gate can be propounded as a useful solution. In the present paper, Flow3D was used to numerically simulate temporal changes of scour in combined free flow over weirs and below gates. Numerical modeling was run after fully preparing and the obtained data was analyzed under three-dimensional conditions. Comparing experimental and numerical results with data fitness revealed that determination coefficient (R2) of the numerical model results to the experimental model results is 0.94. Also, it was found that the relative error of the numerical model results relative to the experimental results equals 7.36%. Further, it was found that at the start of computations in the numerical model, compared to the end of running the model, the turbulent energy dissipation was decreased to 38% and decreasing the turbulent energy dissipation led to the creation of scour hole balance in the numerical model.